KEWENANGAN KREDITUR DALAM KEPAILITAN DEBITUR - , Evi Purwaningsih, SH; , Prof. Dr. Nindyo Pramono, S.H., M.S. ([Yogyakarta] : Universitas Gadjah Mada, 2012)
The purpose of this Study: To know the legal authority of the creditor if the debtor bankrupt. To determine the existence of the debtor in the agreement in general agreement with the existence of the debtor in debts. To find out the status of separatist creditors pursuant to the provisions of Article 56 of Law No. 37 of 2004, following a Supreme Court Decision Number: 124 K/Pdt.Sus/2009. The methods used in analyzing the data is a qualitative method with the type of research is the normative juridical. Qualitatively by considering the facts about bankruptcy cases for further compared with the norms that should apply and then be concluded. Juridical normative because it refers to the legal norms contained in legislation and court decisions and legal norms that exist in society. Conclusion: The result of the bankruptcy decision, then that must be considered is the right to immediately take precedence in return of payment of other creditors against the sale of an item of disputes. Assurance against material creditor rights holders even have the privilege to have no legal guarantee means you can have and/or request objects upon which there is a right guaranteed to be removed from the bankruptcy estate. Debtor position in engagement is generally the same as the position of the debtor in a debt agreement, it is known that if the debtor is unable to repay their debts, then he was imprisoned, but if the debtor has a property in the future, then it must be able to pay off her debts. Creditors who have facilities in case of bankruptcy, its distribution is dependent creditor rights holders, unions and the State in this case the Minister of Finance/Tax, where they are a preferred creditor. In interpreting and applying the provisions of Article 56 of the Bankruptcy Act, beyond the amendment provisions of Article 56 of the Bankruptcy Act, the most logical thing to do is to explain the position of Article 56 of the Bankruptcy Act to the relevant provisions of other laws, so that differences in interpretation of the related-party can be minimized.